Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.4252/wjsc.v6.i5.629
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell application for osteoarthritis in the knee joint: A minireview

Abstract: Knee osteoarthritis is a chronic, indolent disease that will affect an ever increasing number of patients, especially the elderly and the obese. It is characterized by degeneration of the cartilage substance inside the knee which leads to pain, stiffness and tenderness. By some estimations in 2030, only in the United States, this medical condition will burden 67 million people. While conventional treatments like physiotherapy or drugs offer temporary relief of clinical symptoms, restoration of normal cartilage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 68 publications
0
44
0
Order By: Relevance
“…21 Currently, the capacity of MSCs to provide clinical benefits is unclear. 22 Our novel autologous conditioning processing, Arthrokinex TM (ACS), and subsequent standardized protocol, was developed following the success of treatment strategies such as Orthokine and Arthrex that induced IL-1-Ra from whole blood. 10,11 Arthrokinex TM (ACS) offers an interventional orthopedic treatment plan at the molecular level and it incorporates the inhibition of IL-1b through the rapid induction of IL-1-Ra.…”
Section: -14mentioning
confidence: 99%
“…21 Currently, the capacity of MSCs to provide clinical benefits is unclear. 22 Our novel autologous conditioning processing, Arthrokinex TM (ACS), and subsequent standardized protocol, was developed following the success of treatment strategies such as Orthokine and Arthrex that induced IL-1-Ra from whole blood. 10,11 Arthrokinex TM (ACS) offers an interventional orthopedic treatment plan at the molecular level and it incorporates the inhibition of IL-1b through the rapid induction of IL-1-Ra.…”
Section: -14mentioning
confidence: 99%
“…Furthermore, regenerated cartilage is very fragile, and can be damaged with even a low level of stress to the joints (Gupta et al, 2012). Thus, selfregeneration of cartilage is not only a slow process, but also produces cartilage tissues that are not stable enough to resist intensive use (Uth and Trifonov, 2014). Kim et al (2015) reported that it is possible to artificially stimulate the regeneration process by delivering MSCs to knee joints affected with OA.…”
Section: Introductionmentioning
confidence: 99%
“…The basic pathophysiological characteristic of knee OA is loss of articular cartilage which is linked to biomechanical and biochemical changes in the cartilage of the knee joint such as, diminished ability to withstand normal mechanical stresses, limited supply of nutrients and oxygen, inadequate synthesis of extracellular matrix components, increased synthesis of tissue-destructive proteinases (matrix metalloproteinases and aggrecanase) and overall apoptosis of chondrocytes. 8,9,20,21 Although, recently synovial inflammation has been reported as a factor limiting cartilage repair. 22 Articular cartilage exhibits little or no ability for self-repair, because of the low mitotic ability of chondrocytes, and lack of blood, lymphatic or nerve supply, resulting in progressive tissue loss and dysfunction and presenting as a potential challenge for orthopaedic surgeons.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Osteoarthritis of the knee is the most common chronic condition affecting all races, gender and ages, but known to be the most common in elderly and obese people. 8,9 The knee acts as a conduit for transferring body weight essential for normal human mobility and the menisci is known to maintain the normal function of the knee, distribute load, lubricate the joint and provide joint stability. Injury to the meniscus from ageing cartilage, repetitive activity or trauma results in pain, limits movement and can accelerate the occurrence and development of OA.…”
Section: Introductionmentioning
confidence: 99%